Mathematical analysis of the evaporative process of a new technological treatment of rising damp in historic buildings - A. S. Guimarães (2010)
The treatment of rising damp in historic buildings walls is very complex, due to the thickness and heterogeneity of those walls. The traditionally techniques used to deal with this kind of problem (such as watertight barriers, injection of hydrofuge products, etc.) show, sometimes, to be ineffective, justifying the need to find a new approach. Experimental studies in the area of rising damp validate the effectiveness of a new treatment technique applied to the walls of old buildings. The results of the experiment show that the presence of a wall base ventilation system on both sides prevents the damp front from reaching Level 9 (i.e., a height of 61.5 cm). This work describes the moisture transfer process between a moving air flux and a saturated wall, by both advection and diffusion. Numerical solution of the partial differential equation describing moisture conservation gave the concentration field near the saturated surface and the mass transfer flux was integrated to give values of the Sherwood number as a function of Peclet number. A mathematical expression is proposed (given as Eq. (21) in the paper) to describe accurately the numerical dependence between the value of the Sherwood number and the values of Peclet number.